Estrutura produtiva agropecuária e desempenho econômico urbano nos municípios e regiões do Rio Grande do Sul - Lopes, Lewison Ficagna (2011)
The study of rural urban relationships expose the various forms of interaction between country and city, given the relationship of complementarity between them in the urban areas contributes to rural development, and rural areas contributes to urban development. From this second point of view, this work, through factor analysis, in the years 1996 and 2006, identifies the regions of rural development of Rio Grande do Sul and join them at high, medium development and low development, and realizes that the largest group is the development of greater numbers of urban jobs, followed by groups of medium and low development. The factors of factor analysis are used in econometric models for the years 1996 and 2006, as explanatory variables and the dependent variable is employment by sector, resulting in the confirmation of the relationship between rural infrastructure and the number of jobs in urban certain sectors.